Hypoxia and cancer related pathology. (28th August 2020) - Xiong, Qiuxia; Liu, Baiyang; Ding, Mingxia; Zhou, Jumin; Yang, Cuiping; Chen, Yongbin
Abstract: Hypoxic environments occur normally at high altitude, or in underground burrows and in deep sea habitats. They also occur pathologically in human ischemia and in hypoxic solid tumors. Hypoxia in various cancer types and its related molecular mechanisms are associated with a poor clinical outcome. This review will discuss how hypoxia can influence two aspects of tumorigenesis, namely the direct, cell-intrinsic oncogenic effects, as well as the indirect effects on tumor progression mediated by an altered tumor microenvironment. We will also discuss recent progress in identifying the functional roles of hypoxia-related factors (HIFs), along with their regulators and downstream target genes, in cancer stem cells and therapy. Importantly, we propose, using convergent evolution schemes to identify novel biomarkers for both hypoxia adaptation and hypoxic solid tumors as an important strategy in the future. Highlights: Hypoxia and its related molecular mechanisms play important roles in various human cancers. HIF-1a and HIF-2a regulate cancer cell proliferation, migration, self-renewal and drug resistance abilities. Hypoxia is important for regulating the immunosurveillance of tumor. Hypoxia in solid tumor promotes resistance to cancer therapy.